2020 IEEE Symposium on Security and Privacy (SP) 2020
DOI: 10.1109/sp40000.2020.00084
|View full text |Cite
|
Sign up to set email alerts
|

A Security Analysis of the Facebook Ad Library

Abstract: Actors engaged in election disinformation are using online advertising platforms to spread political messages. In response to this threat, online advertising networks have started making political advertising on their platforms more transparent in order to enable third parties to detect malicious advertisers. We present a set of methodologies and perform a security analysis of Facebook's U.S. Ad Library, which is their political advertising transparency product. Unfortunately, we find that there are several we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…On the other, it is important to stress the platform's structural constraints, which have been previously highlighted by Edelson et al (2020) and Silva et al (2020). Regarding the monetary and audience targeting variables, the data provided by the Facebook Ad Library are simplified and not very accurate, as they are based on numerical ranges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other, it is important to stress the platform's structural constraints, which have been previously highlighted by Edelson et al (2020) and Silva et al (2020). Regarding the monetary and audience targeting variables, the data provided by the Facebook Ad Library are simplified and not very accurate, as they are based on numerical ranges.…”
Section: Discussionmentioning
confidence: 99%
“…The corpus, obtained directly from the Facebook Ad Library, was made up of 14,684 ads published by six Spanish national parties during the two election campaigns. As far as can be gathered from the literature, apart from the research conducted by Edelson et al (2020), this study is among the first to have explored this information source (see also Cano-Orón et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Ribeiro et al [30] analysed ads send by the Russian interference in the 2016 US elections and found that ads were send to people less likely to report them. Edelson et al [9] presented a clustering-based method to discover advertisers engaging in a potentially undeclared coordinated activity and proposed recommendations for improving the security of political advertising transparency. Furthermore, Bolden et al [5] summarized problems with the Facebook Ad Library, such as the lack of clear policies and data systematicity.…”
Section: Related Workmentioning
confidence: 99%
“…Advertisers have little control over ad distribution and are thus mostly unaware of the specific websites where their ads appear. Platforms provide few affordances to audit the targeting and allocation algorithms of this technology, and those few that are available have been found deficient and incomplete (Andreou et al, 2019; Edelson et al, 2020; Matias et al, 2021). Therefore, programmatic advertising involves a reputational risk when ads appear on sites that involve not only brand-misaligned content but also disinformation, hateful statements, or immoral content (Mostrous, 2017).…”
Section: Introductionmentioning
confidence: 99%